PROBLEM YURISDIKSI PELINDUNGAN HAK CIPTA DI ERA DIGITAL (Jurisdiction Problem of Copyright Protection in the Digital Age) - Stevanus Rionaldo; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
Copyright protection is the right provided to authors or owners of copyrighted works to restrict the use of their works. In the digital era, copyright protection has become increasingly important due to the ease of dissemination of copyrighted works online. However, often copyright is not well protected in the online world, especially due to easy access to copyrighted works and rapid dissemination through the internet. The impact of the existence of the internet on the principles of law and jurisdiction that previously relied on physical attributes, such as lex loci, has become irrelevant. As a result, jurisdictional limitations between countries have become more complex in enforcing copyright law violations. Therefore, the development of internet technology encourages social and economic changes that require adaptation in copyright regulations.